3D Hetero-architecture of GdB6 nanoparticles on lessened cubic Cu2O nanowires: enhanced field emission behaviour - Suryawanshi, Sachin R.; Singh, Anil K.; Deo, Meenal S.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (CrystEngComm, 2015)
The field emission properties (FE) of a heteroarchitecture comprised of gadolinium hexaboride nanoparticles uniformly decorated over Cu2O nanoneedles (GdB6/Cu2O) have been investigated at the base pressure of similar to 1 x 10(-8) mbar. Under the optimized pulsed laser deposition (PLD), a well-adhered coating of GdB6 nanoparticles on chemically synthesized cuprous oxide (Cu2O) nanoneedles has been obtained. A plausible growth mechanism of the hierarchical assembly of GdB6 nanoparticles on the Cu2O nanoneedles is explained on the basis of structural analysis carried out using SEM and TEM. A low turn-on field of similar to 2.3 V mu m(-1) (to draw an emission current density similar to 1 mu A cm(-2)) is observed along with stable emission current at the preset value of similar to 2 mu A over 4 h. The enhanced emission behaviour of the GdB6/Cu2O heteroarchitecture, in contrast to the pristine Cu2O nanoneedles, is attributed to its high aspect ratio and low work function. The observed FE results demonstrate GdB6/Cu2O heteroarchitecture as a potential candidate for application in various vacuum nano/microelectronic devices.